Diet And Lifestyle For The Elderly With Comorbidities Before And During The Covid-19 Pandemic - Damayanti, Galuh; Kaswari, Sutomo Rum Teguh; adelina, rany (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Objectives: This study aims to determine diet and lifestyle of the elderly with comorbidities before and during the covid-19 pandemic.Methods: This study used a descriptive cross-sectional study design. This study was conducted in one of the working areas of the Gondang Health Center, namely the elderly posyandu of Ngrendeng Village, Gondang District, Tulungagung Regency, East Java, Indonesia on November 29, 2021 to December 10, 2021. The sample used the purposive sampling of 40 subjects. The instrument used is form of a questionnaire (google form). Data analysis uses bivariate, univariate, and multivariate analysis. Results: There was no significant difference between feeding frequency of the elderly with comorbidities before and during the covid-19 pandemic (p>0.05). Meanwhile, the type of food consumed, activity patterns, cleanliness of the living environment, and personal hygiene of the elderly with comorbidities have significant differences between before and during the covid-19 pandemic (p<0.05).Conclusion: Overall, there have been significant differences between the diet and lifestyle of the elderly before and during the covid-19 pandemic.